Strategies for economic empowerment via BUMDes: A path to sustainable development in Renah Alai Village - Umiyati, Etik; Zulgani, Zulgani; Prasetyo, Eko (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2023)
The BUMDes, a village business entity managed by local communities, bolsters local economies and is established based on village-specific needs and potential. While the BUMDes in Renah Alai remains nascent, its contributions to the village's development and local community welfare have been limited. For the enduring success of the community, an empowerment strategy for BUMDes involving the government, village officials, and local stakeholders should accentuate rural local wisdom, encompassing socio-demographic constructs, agricultural enterprises, and village institutional frameworks. This research sought to conceptualize and dissect the paradigm of village economic enhancement via BUMDes in Renah Alai, targeting sustainable village growth. The SWOT-AHP analytical tool was employed, with the AHP approach yielding strategic recommendations through the SWOT matrix. Data was amassed via surveys and comprehensive interviews and processed through Focus Group Discussions (FGD) with pertinent village agencies and officials. The SWOT matrix's cumulative weights revealed that the Weakness-Opportunity strategy matrix was paramount, marking it as a cornerstone for the Renah Alai BUMDes Empowerment roadmap. The SWOT-AHP analysis delineated four pivotal empowerment areas for BUMDes in Renah Alai: 1) Institutional fortification of BUMDes, 2) Human resource quality enhancement, 3) Infrastructure, and 4) Capital acquisition.